Experimental investigation and analytical modelling of blind bolted flush or extended end plate connections to circular CFDST columns. (1st August 2019) - Guo, Lei; Wang, Jingfeng; Wu, Shuncheng; Zhong, Liping
Highlights: Cyclic tests on circular CFDST column blind bolted end plate joints were conducted. Failure mechanism and seismic behavior of the connections were analyzed. Analytical models were proposed to estimate the mechanical behavior of connections. Abstract: An experimental program was carried out to investigate the seismic performance and analytical modelling of blind bolted flush or extended end plate connections to circular concrete filled double skin steel tubular (CFDST) columns. A series of cruciform assemblage specimens composed of circular CFDST columns and H-shaped steel beams were tested under lateral cyclic loads. The test parameters were determined as the curved end plate type and column hollow ratio. Typical failure modes for the connections to CFDST columns were analyzed by comparing with blind bolted connections to CFST columns, which indicated CFDST column blind bolted to steel beam connections significantly restricted the outward deformation of column wall. Moreover, the seismic performance of blind bolted connections between circular CFDST columns and steel beams was also estimated in terms of the moment ( M ) -rotation ( θ r ) relationship curves, ductility and energy dissipation capacities. Besides, the failure mechanism was studied through the analysis of strain responses. Analytical models were calibrated to estimate the initial stiffness and moment resistance of the blind bolted connections, which focused on the stiffness coefficients of curved flush and extended end plates in bending and the influence of circular CFDST column. The analytical models were verified against the experimental results. The experimental and analytical results indicated that the blind bolted flush or extended end plate connections to circular CFDST columns had superior seismic behavior and properly could meet the design demands in high-intensity seismic regions.